Robust extraction of biological information from diffusion-weighted magnetic resonance imaging during radiotherapy using semi-automatic delineation. (January 2022) - Bisgaard, Anne Louise Højmark; Brink, Carsten; Fransen, Maja Lynge; Schytte, Tine; Behrens, Claus P.; Vogelius, Ivan; Nissen, Henrik Dahl; Mahmood, Faisal
Highlights: An intensity-based delineation tool for consistent ADC measurements is presented. Semi-automatic delineation performs comparable to manual expert delineation. Intra-treatment ADC changes may reflect radiotherapy induced biological changes. Abstract: Background and purpose: Diffusion-Weighted Magnetic Resonance imaging (DWI) quantifies water mobility through the Apparent Diffusion Coefficient (ADC), a promising radiotherapy response biomarker. ADC measurements depend on manual delineation of a region of interest, a time-consuming and observer-dependent process. Here, the aim was to introduce and test the performance of a new, semi-automatic delineation tool (SADT) for ADC calculation within the viable region of the tumour. Materials and methods: Thirty patients with rectal cancer were scanned with DWI before radiotherapy (RT) (baseline) and two weeks into RT (week 2). The SADT was based on intensities in b=1100 s mm −2 DWI and derived ADC maps. ADC values measured using the SADT and manual delineations were compared using Bland-Altman- and correlation analyses. Delineations were repeated to assess intra-observer variation, and repeatability was estimated using repeated DWI scans. Results: ADC measured using the SADT and manual delineation showed strong and moderate correlation at baseline and week 2, respectively, with the SADT measuring systematically smaller values. Intra-observer ADC variation was slightly smaller for the SADT compared to manual delineation both at baseline, [−0.00; 0.03] vs. [−0.02; 0.04] 10 −3 mm 2 s −1, and week 2, [−0.01; 0.00] vs. [−0.04; 0.07] 10 −3 mm 2 s −1 (68.3% limits of agreement). The ADC change between baseline and week 2 was larger than the ADC uncertainty ( ± 0.04 · 10 −3 mm 2 s −1 ) in all cases except one. Conclusion: The presented SADT showed performance comparable to manual expert delineation, and with sufficient consistency to allow extraction of potential biological information from the viable tumour.